Performa reproduksi ayam ras petelur yang diberi berbagai tingkat ekstrak daun Belimbing Wuluh - Annisa Putri Cahyani; Shania Ayu Suzana; Dewi Pranatasari; Suci Andanawari; Muzizat Akbarrizki; Ari Novitasari; Dwi Novrina Nawangsari; Edi Purwono (Fakultas Pertanian Universitas Majalengka, 2026)
The objective of this study was to investigate the influence of Averrhoa bilimbi leaf extract towards the reproductive organ characteristics and the egg quality in laying hens, based on mature follicle numbers, ovary weight, yolk colour, yolk index and egg fertility. The experiment was performed for 9 weeks in the Poultry Laboratory of Polbangtan Yogyakarta Magelang using a completely randomised design (CRD) with four treatments (P0 = control, P1 = 0.5 mg, P2 = 1 mg, P3 = 1.5 mg) and five replications. ANOVA and Duncan’s multiple range test were used for data analysis, and yolk colour was tested by the Kruskal-Wallis method. The extract demonstrated statistically significant influence (p<0.05) on ovary weight, yolk colour, yolk index, fertility and number of mature follicles. The P3 treatment showed the highest values for mature follicles (7.0±0.7), ovary weight (59.54±6.15 g), yolk colour (11.20±0.45), yolk index (0.34±0.01), and fertility (78.33±19.9%). These results indicate that Averrhoa bilimbi leaf extract has a beneficial influence on reproductive performance and egg quality in laying hens.